Health information system / Mohd Fazlee Ghouse Mohamad Khader - Mohd Fazlee Ghouse, Mohamad Khader (2003)
Health Information System or IDS is a database electronic system designed specially to manage information regarding patients and medicine in an outpatient department. This Health Information System also acts as a computerized inventory system to manage medicine in outpatient department that offers health care treatments. This Health Information System is using the stand-alone approach. It is designed based on a user-friendly concept. It also has an interesting interface design and also a professional look that is easy for users to use the system and to manipulate the data stored in the system. Hopefully this system that uses a back-end database would be able to replace the manual system for managing patient information. Users will no longer have to use the manual traditional recording method that takes time to find and to update records and might also result in data redundancy in recording patients' information. Besides this, IDS is also equipped with security preferences that will protect the integrity of the system by only allowing authorized users to access the system. IDS is also able to reduce paper requirements in recording data towards developing a paperless environment.